Taylor's Pig-Tale: A Historical Analysis of Frederick W. Taylor's Pig-iron Experiments - Wrege, Charles D.; Perroni, Amedeo G. (Academy of Management Journal, 1974)
Frederick Taylor is cited as the father of scientific management. His account of the loading of pig-iron has been accepted virtually without question. An investigation of that story reveals it to be more fiction than fact. The authors suggest that management history may require reevaluation based on careful research and analysis.